2018–2019 Florida Citrus Production Guide: Nematodes - Larry W. Duncan; Joseph W. Noling; Renato N. Inserra (EDIS)
Integrated pest management (IPM) for nematodes requires: 1) determining whether pathogenic nematodes are present within the grove; 2) determining whether population densities of some nematodes are high enough to cause economic loss; and 3) selecting a profitable management option. Attempting to manage nematodes may be unprofitable unless the above procedures are carefully followed. Similarly, some management methods pose risk to people and the environment, therefore it is important to know that their use is justified by the actual conditions in a grove. This 3-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Larry W. Duncan, Joe W. Noling, and Renato N. Inserra, and published by the Entomology and Nematology Department, May 2018.